The Effect of Patient Self-Esteem on The Motivation to Treat Diabetic Foot Ulcers - Mardhiah; Sidabutar, Rina Rahmadani (Caring: Indonesian Journal of Nursing Science, 2022)
Diabetic foot ulcers negatively impact the self-esteem of diabetes mellitus patients. Their self-esteem affects their motivation to recover. This was caused by the intention of being negative towards themselves. It affecst the instrinsic motivation of the patients. This study used a questionnaire to obtain the data. Frequency distribution and Spearman Rank (Rho) correlation test with a significant level of 5% were used as the statistical tests. Spearnman Rank result test was p-value=0.000 with a correlation coefficient of 0.0519. Based on the study results, it can be conluded that there is an effect of patient self-esteem on their motivation to treat diabetic foot ulcers at Asri Wound Care Center Medan.